2013
DOI: 10.1111/btp.12082
|View full text |Cite
|
Sign up to set email alerts
|

Altitudinal Patterns in Two Syntopic Species of Sturnira (Mammalia: Chiroptera: Phyllostomidae) in the Montane Rain Forests of Argentina

Abstract: We evaluated altitudinal segregation in two Sturnira species as a mechanism allowing their coexistence. Tests were devised to discern between interspecific interactions and regional responses to geographic and environmental variables, using extensive capture data from 18 montane rain forest sites. No significant correlation between captures was found. Additionally and according to the hypothesis of historical occupation of highland versus lowland forests, each species has shown specificity in their response to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 27 publications
1
5
1
2
Order By: Relevance
“…However, this relationship doesn't always exist or isn't significant (Sánchez and Giannini, 2014). Based on results from the present study, there was no evidence that would suggest that there is an effect of rainfall on the activity level of bats from the understory in the BFR.…”
Section: Bats Activity and Environmental Factorscontrasting
confidence: 80%
See 3 more Smart Citations
“…However, this relationship doesn't always exist or isn't significant (Sánchez and Giannini, 2014). Based on results from the present study, there was no evidence that would suggest that there is an effect of rainfall on the activity level of bats from the understory in the BFR.…”
Section: Bats Activity and Environmental Factorscontrasting
confidence: 80%
“…Variations in air temperature are tightly linked to altitude (Graham, 1983;Soriano, 2000), as has been reported in several studies, is one of the environmental factors that strongly influences bat activity levels (O´Farrell et al, 1967;O´Farrell and Bradley, 1970;O´Shea and Vaughan, 1977;Soriano, 2000;Sánchez and Giannini, 2014). The variation in the temperature range registered in BFR was narrow, compared to historical records, which is characteristic of montane environments; however, our results showed that a greater number of individuals were captured at higher air temperatures, which suggests that air temperature had a significant and positive relationship on the activity of understory bats in cloud forests.…”
Section: Bats Activity and Environmental Factorsmentioning
confidence: 87%
See 2 more Smart Citations
“…Because flight is a very expensive type of locomotion (Norberg 1995), resource availability may limit bat activity; for example, frugivorous bats reduce their foraging activity to preserve energy during periods of food scarcity (Ramos Pereira et al 2010). Climatic conditions may be determinant of abundance or presence of some species; for example, temperature range, maximum temperature of the warmest month and annual mean temperature determine the altitudinal distributions and abundances of Sturnira lilium and S. erythromos in the Yungas (Sánchez and Giannini 2014). Temperature seasonality is important in determining the latitudinal richness of Phyllostomid bats in the Atlantic forest (Stevens 2013).…”
Section: Discussionmentioning
confidence: 99%